TURMERIC EXTRACT EFFECTIVENESS WHITE (CURCUMA DOMESTICA .VALL ) FOR TREATMENT OF BACTERIAL INFECTIONS IN VIBRIO ALGINOLYTICUS MOUSE GROUPER (CROMILEPTES ALTIVELIS) - Dwi Agung Saputra; Elfa Verda Puspita (PT. Jurnal Center Indonesia Publisher, 2024)
This study were aimed to (1) To study the effectiveness of white turmeric extract Curcuma domestica .Vall in treating a mouse Cromileptes altivelis from the attack of Vibrio alginolyticus., (2) To study the dose of the best white turmeric extract in treating a Cromileptes altivelis from attacks by bacteria Vibrio alginolyticus. (3) To study the effect of white turmeric extract against the survival rate Mouse grouper (Cromileptes altivelis), which in the infection of Vibrio alginolyticus. The experiment was arranged with a Completely Randomized Design (CRD). Preliminary research conducted LD50 test to determine the pathogenic bacterium V. alginolyticus which caused the death of test fish as much as 50%. In vitro test was done to see anti-bacterial activity of white turmeric extract against V. alginolyticus. From this test, the optimum concentration of white turmeric extract the effective tackling of V. Alginolyticus was obtained was obtained Test in vivo was carried out to determine the effect of the bacteria V. alginolyticus against Cromileptes altivelis healing response in Cromileptes altivelis after giving white turmeric extract. Results showed that (1) MIC and MBC values obtained by concentration of 0.25% and 0.75%, where the concentration of 0.75% was the effective dose of white turmeric extract in tackling the V. alginolyticus (2) The best treatment dose of the best survival rate of Cromileptes altivelis was 1% of white turmeric extract (3) the Survival Rate of mouse grouper wasn’t effected by white turmeric extract treatment significantly